A Multiple-Case Simulation Module to Support a Second-Year Medical Student Respiratory Curriculum (Out of Print) - Raymond Ten Eyck; Michael Markus; Timothy Janz; Corey Heitz; Melissa Schloneger; Nick Ritucci (Association of American Medical Colleges, 2010)
Abstract Introduction The resource is a simulation exercise designed to support clinical application of the principles from the second-year medical school respiratory system curriculum. The primary educational goals of the resource are to provide a simulated clinical environment in which to discuss pathophysiology, identify signs and symptoms, and demonstrate the basic diagnostic and therapeutic approach to traumatic and mechanical respiratory disorders. The simulation includes four cases regarding spontaneous pneumothorax, smoke inhalation, aspiration pneumonia, and airway compromise due to anaphylaxis. Methods Students complete the cases in an emergency department setting in four groups of six students each. One student group is in the lab for each case and has an opportunity to provide hands-on care with a faculty preceptor in the room. The remaining students observe from an adjacent classroom with an audiovisual feed. A new group rotates into the lab for each case. Results This resource was anonymously assessed by 92 second-year medical students completing a team-based learning exercise using this simulation. The responses were universally positive. The median scores of the student responses was 4 using a 4-point Likert scale (1 = Strongly Disagree; 4 = Strongly Agree) for each of six questions assessing various aspects of the perceived value of the exercise. Discussion The resource is a simulation exercise designed to support clinical application of the principles from the second-year medical school respiratory system curriculum. As such, students rotate through cases of spontaneous pneumothorax, smoke inhalation, aspiration pneumonia, and airway compromise due to anaphylaxis.